Reducing Production Costs by Minimizing Errors in the Operational Production: A Case Study of Company Vendom - Đukanović, Sandra; Lečić-Cvetković, Danica; Rajković, Teodora (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Errors in operational production cannot be entirely eliminated, but they can be minimized to reduce their impact on production costs. These errors can affect several aspects, including increased material costs, waste generation, product quality, delivery delays, company reputation, and customer dissatisfaction. By identifying the root causes and applying various methods and techniques, it is possible to determine the most critical and frequent errors in operational production and develop effective corrective measures. The purpose of this study is to illustrate, through the example of the company Vendom, how to minimize costs arising from errors in the operational production, using the FMEA method for error identification. The results of the study is a proposed set of measures to reduce errors in operational production. These measures have a direct impact on reducing production costs.